Sewage Recent Advances, New Perspectives and Applications - Zhang, Tao (IntechOpen, 2022)
Wastewater treatment is crucial for human development. The current state of development of wastewater, the current state of its impact, and the current state of development of wastewater treatment methods are to be closely followed. This book compiles some of the cutting-edge developments related to wastewater treatment.